1984
DOI: 10.1177/000348948409300310
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Otorrhagia and Orbital Hematoma Complicating Subgaleal Hematoma

Abstract: A patient with bilateral otorrhagia and orbital hematoma following massive subgaleal hematoma is reported for the first time. The pathogenesis of the extensive subgaleal hematoma as well as the production of these unusual complications is discussed. This case would suggest that the weakest points in the attachment of the epicranial aponeurosis to the base of the calvarium are its attachments to the squamous part of the temporal bone and to the frontal bone under the eyebrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…4 -6 Reports of orbital extension are scarce and usually related to blunt head trauma. 4 We report a case of subgaleal hematoma with orbital extension that resulted from the relatively minor trauma of hair pulling.…”
mentioning
confidence: 99%
“…4 -6 Reports of orbital extension are scarce and usually related to blunt head trauma. 4 We report a case of subgaleal hematoma with orbital extension that resulted from the relatively minor trauma of hair pulling.…”
mentioning
confidence: 99%
“…These patients may exhibit irritability, lethargy, hypotonia and seizures [13,19] . Rarely reported complications of SGH include otorrhagia, retro-orbital hematoma, and jaundice from breakdown of hemoglobin [20,21] . Subgaleal abscesses are well described in the literature, with the most common causes being fetal scalp monitoring, mistreated scalp lacerations, postoperative infection, and needle aspiration of an SGH [6,22] .…”
Section: Discussionmentioning
confidence: 99%
“…All 11 had surgery. Six patients returned to 20/20 vision after surgery; 1 improved to 20/30, 12 1 remained no light perception, 5 1 was lost to follow-up, 13 and for 2 it was only indicated that "orbital swelling resolved" without a note of visual acuity. 10,14 Six reported cases had bleeding disorders: 15 (Factor IX deficiency [Christmas disease] 16 and heterozygous Factor VII deficiency).…”
Section: Discussionmentioning
confidence: 99%
“…17 No bleeding anomaly was found in our patient. Other reported associations include sickle cell disease, vitamin C deficiency, 6 hypertension, 13 and thrombocytopenia secondary to congenital heart disease. 18 Child abuse should be considered when evaluating SGH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation